Vectorization of hand drawn line drawings for animation - Foo, Ce Rong. (2011)
In 2D animation production, animators usually make sketches before cleaning up to get the final frames. The sketching is done using either pen and paper, or digital input devices, e.g. digital tablets. This unconstrained sketching in early design offers maximum freedom possible and is usually in raster representation. On the other hand, vector-based graphics becomes more and more popular. Vector representation provides a compact mathematical description of lines and is suitable for subsequent operations e.g. editing, inbetweening and colouring. Animation drawings are quite different, composed of freeform shapes. An application using edge detection algorithm will be written to provide a means to help artists to reduce the work required to vectorize their sketches via tracing tools. This project will focus on the insight of the research on curve structure extraction for cartoon images as well as its implementation and development. The aim is to develop an effective and efficient approach to automatically vectorize sketches into clean vector-based line drawings.